Mineralogy, petrology, and oxygen isotopic compositions of aluminum-rich chondrules from unequilibrated ordinary and the Dar al Gani 083 (CO3.1) chondrite. (1st November 2022) - Ebert, Samuel; Nagashima, Kazuhide; Bischoff, Addi; Berndt, Jasper; Krot, Alexander N.
Abstract: Understanding the genetic relationship between different chondritic components will help to decipher their origin and dynamical evolution within the protoplanetary disk. Here, we obtain insight into these processes by acquiring O-isotope data from 17 Al-rich chondrules from unequilibrated ordinary chondrites (OCs, petrologic type ≤ 3.2) and four Al-rich chondrules from the CO3.1 carbonaceous chondrite Dar al Gani (DaG) 083. These particular kinds of chondrules are of special interest, as it is suggested that their precursors may have contained refractory material related to Ca, Al-rich inclusions (CAIs) and amoeboid olivine aggregates (AOAs). The four investigated Al-rich chondrules from the CO3.1 chondrite Dar al Gani 083 consist of olivine, low-Ca pyroxene, Ca pyroxene, and spinel phenocrysts embedded in mostly Na-rich glassy mesostasis. Two chondrules have a homogeneous O-isotopic composition and two are heterogeneous in their O-isotopic composition. One chondrule contains relict spinel grains with a Δ 17 O value of −24.3 ± 1.3‰, indicative of 16 O-rich precursor refractory material, similar to constituents of CAIs and AOAs. The presence of CAI-like precursors for the Al-rich chondrules from CO chondrites is consistent with their previously reported presence of 50 Ti excesses (Ebert et al., 2018). The Al-rich chondrules in the ordinary chondrites studied consist of olivine, low-Ca pyroxene, Ca pyroxene, and, occasionally, spinel phenocrysts embedded in mostly Na-rich glassy mesostasis. Hibonite is present in one Al-rich chondrule. The vast majority of these chondrules have heterogeneous O-isotopic compositions: Chondrule glasses are 16 O-depleted compared to chondrule phenocrysts; the Δ 17 O values of the former approach those of aqueously formed fayalite and magnetite grains in type 3 OCs, ∼ +5‰. We infer that the chondrule glasses experienced O-isotope exchange with an aqueous fluid on the OC parent asteroids. Chondrule phenocrysts, like spinel, olivine, low-Ca pyroxene, and Ca pyroxene, were not affected by this isotope exchange and preserved their initial O-isotope compositions. The phenocrysts within individual chondrules have similar Δ 17 O, whereas the inter-chondrule Δ 17 O values range from −4.5 to +1.4‰, i.e., they are in general 16 O enriched relative to the majority of ferromagnesian type I and type II porphyritic chondrules in OCs having Δ 17 O of ∼ +1‰. Because no relict grains were identified in the Al-rich chondrules from ordinary chondrites, the original O-isotopic composition of the refractory precursor material remains unknown. Additional detailed Na measurements within olivine grains show no major changes in the Na content of the chondrule melt during their crystallization. This implies either that the Na was part of the precursor material or that the Na was enriched in the chondrule melt/glass after crystallization of the olivines.